2017
DOI: 10.1021/acs.est.7b00369
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Characteristics of Microplastic Pollution in Xiangxi Bay of Three Gorges Reservoir, China

Abstract: Microplastic pollution in inland waters is receiving growing attentions. Reservoirs are suspected to be particularly vulnerable to microplastic pollution. However, very limited information is currently available on pollution characteristics of microplastics in reservoir ecosystems. This work studied the distribution and characteristics of microplastics in the backwater area of Xiangxi River, a typical tributary of the Three Gorges Reservoir. Microplastics were detected in both surface water and sediment with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
130
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(145 citation statements)
references
References 53 publications
12
130
0
3
Order By: Relevance
“…The lowest counts were collected at nonurban coastal stations and offshore basin stations, with the exception of the deepest point of the Eastern Basin of Lake Erie (Figures 3, 4B). These findings support previous reports of a correlation between plastic concentrations and proximity to urban centers in the Great Lakes (Baldwin et al, 2016), as well as other enclosed and semi-enclosed aquatic environments across the world, such as, tributaries to the Chesapeake Bay, USA (Yonkos et al, 2014), the Bay of Brest in France (Frère et al, 2017), the Xiangzi Bay upstream of the three Gorges Dam (Zhang et al, 2017), inland lakes around Wuhan, China (Wang et al, 2017), and estuaries in and around Durban, South Africa (Naidoo et al, 2015). Attributes that are likely to contribute to elevated plastic concentrations in urban vs. nonurban locales include higher population densities (Jambeck et al, 2015), increased particulate aeolian inputs (including plastic; Dris et al, 2015), and increased areas of impervious substrate.…”
Section: Plastic Concentrations Were Highest At Urban Centerssupporting
confidence: 91%
See 1 more Smart Citation
“…The lowest counts were collected at nonurban coastal stations and offshore basin stations, with the exception of the deepest point of the Eastern Basin of Lake Erie (Figures 3, 4B). These findings support previous reports of a correlation between plastic concentrations and proximity to urban centers in the Great Lakes (Baldwin et al, 2016), as well as other enclosed and semi-enclosed aquatic environments across the world, such as, tributaries to the Chesapeake Bay, USA (Yonkos et al, 2014), the Bay of Brest in France (Frère et al, 2017), the Xiangzi Bay upstream of the three Gorges Dam (Zhang et al, 2017), inland lakes around Wuhan, China (Wang et al, 2017), and estuaries in and around Durban, South Africa (Naidoo et al, 2015). Attributes that are likely to contribute to elevated plastic concentrations in urban vs. nonurban locales include higher population densities (Jambeck et al, 2015), increased particulate aeolian inputs (including plastic; Dris et al, 2015), and increased areas of impervious substrate.…”
Section: Plastic Concentrations Were Highest At Urban Centerssupporting
confidence: 91%
“…These findings are consistent with surveys of other lakes, such as, lakes near Wuhan, China where more than 80% of the plastics found were 2 mm and smaller (Wang et al, 2017). However, plastics 1-5 mm in size were most abundant in sections of the Xiangxi River, perhaps due to a shorter residence time and less weathering while in the river (Zhang et al, 2017). Previous surveys of Great Lakes plastic have found a 40-and 6-fold difference between the smallest and largest size classes (Eriksen et al, 2013;Mason et al, 2016).…”
Section: Plastic Less Than 1 MM Dominated the Datasetsupporting
confidence: 89%
“…Plastic debris was observed in 141 gastrointestinal tracts of fish samples (n = 279) covering all 9 fish species with a detection frequency of 15.8 to 75.0%, and a total of 1945 particles were extracted with a mean abundance of 7.0 ± 23.8 (±SD) items per individual (range not detected-247 items/individual; Table 1), indicating that plastic ingestion was omnipresent in wild freshwater fish in the Pearl River catchment. The detection frequencies observed in the present study were higher than those of fish from French rivers (12%; Sanchez et al 2014); comparable to those of fish from the Three Gorges Reservoir of China (25.7%; Zhang et al 2017), the English Channel (36.5%; Lusher et al 2013), and the River Thames (∼76%; McGoran et al 2017); and lower than those of fish from Taihu Lake, the Yangtze River estuary, and the South China Sea (95.7-100%; Jabeen et al 2017). However, the detected abundance of plastic debris in the wild freshwater fish from the Pearl River catchment was higher than that in coastal and freshwater fish from southeast China (Jabeen et al 2017); freshwater fish from the Three Gorges Reservoir (Zhang et al 2017); marine mussels from Avery Point, Connecticut, USA (Zhao et al 2018); and tadpoles from small water bodies of the Yangtze River delta, © 2019 SETAC wileyonlinelibrary.com/ETC China (Hu et al 2018), suggesting more serious plastic pollution in the Pearl River catchment.…”
Section: Occurrence Of Plastic Debris In Freshwater Fishsupporting
confidence: 67%
“…Microplastic concentrations were negatively correlated with water velocity. The authors hypothesized that dams might contribute to accumulations of less dense microplastics, as did K. Zhang et al () investigating distributions of microplastics in the Yangtze River near the Three Gorges Dam in China. McCormick et al () observed microplastic concentrations increased from upstream (1.94 ± 0.81 particles m −3 ) to downstream (18 ± 11 particles/m 3 ) sites in the Illinois River, a tributary of the Mississippi.…”
Section: Microplastics In Freshwatersmentioning
confidence: 95%